MODERATING EFFECT OF INFORMATION TECHNOLOGY UTILIZATION ON THE RELATIONSHIP BETWEEN COMMITMENT AND CUSTOMER SATISFACTION - Boise Nyameino, Charles; Bonuke, Ronald; Kimeli Cheruiyot, Thomas (British Journal of Marketing Studies, 2015)
Commitment is an essential ingredient for successful long-term relationships between customer satisfaction and information communication technology utilization. Developing Customer’s commitment in business relationships pays off in increased profits, customer retention, willingness to refer and recommend. Practitioners and scholars have identified customer value as a pivotal issue in the management of hotel business relationships. Of late the hospitality industry has witnessed growing interest in relationship marketing, customer satisfaction and information communication technology utilization. Although relationship marketing has been identified as an effective strategy to attract, maintain and enhance customer relationships, there are few empirical studies that have tested the underlying assumptions on classified star hotels of the relationship marketing research is based on. The aim of this study was to determine the moderating effect of information technology communication (ICT) utilization on the relationship between commitment and customer satisfaction by classified hotels. Descriptive research design was adopted for this study. The target population was 6067 customers at classified star hotels in Nairobi Kenya and a sample size of 375 was obtained using proportionate sampling from five categorized star hotels. Data was collected using a 5 Likert-scale questionnaire. Data was analyzed using multiple regression analysis. The study revealed that commitment strategy significantly affects customer satisfaction (?= .309, p-value = 0.001) thus the study rejected H01 since ??0 and p-value was less than ?. The moderating effect of Information Technology Utilization explained 5.7% variance in Customer Satisfaction above and beyond the variance by commitment strategy scores. H02 was rejected since ??0 and p-value was less than ?. This study concluded that commitment strategy as an element of relationship marketing practices significantly affects customer satisfaction. This study recommends that classified star hotels managers should develop high levels of affective commitment and calculative commitment to build the strongest relationships with customers. Important factors of commitment include creating attachment, flexibility and a good environment for the customers.